NAVIGATING GREY ZONES: INTEGRITY VULNERABILITIES IN REGIONAL GOVERNANCE - Rifqi Novriyandana; Iwan Alfanie; Sunardi; Reja Fahlevi; Dewi Sri Susanti; Arif Rahman Hakim; Muhammad Baqir; Muhamad Rafli (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
Formal integrity systems often fail to produce ethical outcomes in decentralized bureaucracies, giving rise to what this study conceptualizes as an